RF radiation safety handbook - Kitchen, Ronald (Butterworth Heinemann, 1993)
A guide for radio, mechanical, medical, or other engineers who are responsible for or concerned about the possible dangers of radio frequency radiation, including electromagnetic compatibility and interference, electro- explosive vapors and devices, and direct effects on the human body. The topics include sources and effects, safety standards (British, European, and US), radiation surveys and measurement, and designing antennas and other devices.
Keywords: Radio frequency -- Safety measures.; Radio frequency -- Physiological effect.; Radiation -- Safety measures.; Radiation -- Physiological effect.; elektronické knihy; electronic books